Pentadecyl phenol- and cardanol-functionalized fluorescent, room- temperature liquid-crystalline perylene bisimides: effect of pendant chain unsaturation on self-assembly - Bhavsar, Ghanashyam A.; Asha, S. K. (Chemistry - A European Journal, 2011)
A new perylene bisimide (PBI) building block based on pentadecyl phenol (PDP) or cardanol was developed, which upon esterification with 3,4,5-tridodecyloxy gallate resulted in highly emissive, room-temperature liquid-crystalline (LC) molecules. The self assembly in solution was studied in detail by NMR spectroscopy, UV/Vis absorption, and fluorescence spectroscopy. In solution both PDP- and cardanol-based PBI exhibited similar behavior. They were molecularly dissolved in chloroform (CHCl3) but formed rotationally displaced H-type aggregates that emitted at 640 nm in methylcyclohexane (MCH). Surface morphology in dropcast films were characterized using microscopic techniques such as SEM, TEM, and atomic force microscopy (AFM). The liquid-crystalline properties were studied using differential scanning calorimetry (DSC), polarized light microscopy (PLM), and variable-temperature X-ray (small-angle X-ray scattering (SAXS) and wide-angle X-ray diffraction (WXRD)) studies. Variable-temperature X-ray studies in the LC phase indicated strong π–π stacking interaction present in the PDP-based PBI derivative, whereas the stacking was absent in the LC phase of the cardanol-based PBI. The latter formed self-organized structures of extremely short length due to the presence of cis double bonds in the C15 alkyl side chain, whereas the saturated alkyl side chain in PDP could pack efficiently, thereby resulting in nanofibers that were several micrometers in length.